1992
DOI: 10.1152/ajpcell.1992.263.2.c545
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence localization of the Na-Ca exchanger in heart cells

Abstract: We investigated the localization of the Na-Ca exchanger in fixed, isolated heart cells from rat and guinea pig using immunocytochemical methods with epifluorescence and confocal microscopy. We found that the Na-Ca exchanger is distributed throughout all membranes in contact with the extracellular space, including the sarcolemma, the transverse tubules (T-tubules), and the intercalated disks. Microscopic nonuniformities in the fluorescent labeling appear to reflect varying views of the membranes containing Na-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
45
1
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 22 publications
10
45
1
2
Order By: Relevance
“…NCX1 was identified in the sarcolemmal membrane and in the Z-lines of cardiomyocytes (Fig. 5) as already reported (48,49). Interestingly, mAKAP is also localized in the Z-lines and the dual staining of NCX1 and mAKAP confirmed that both of these proteins are present in the same location in rat cardiomyocytes (Fig.…”
Section: Localization Of Ncx1 Makap and Pka-ri In Rat Cardiomyocytessupporting
confidence: 83%
See 1 more Smart Citation
“…NCX1 was identified in the sarcolemmal membrane and in the Z-lines of cardiomyocytes (Fig. 5) as already reported (48,49). Interestingly, mAKAP is also localized in the Z-lines and the dual staining of NCX1 and mAKAP confirmed that both of these proteins are present in the same location in rat cardiomyocytes (Fig.…”
Section: Localization Of Ncx1 Makap and Pka-ri In Rat Cardiomyocytessupporting
confidence: 83%
“…There is also the possibility that AKAPs can directly bind to the cytoskeleton as was demonstrated for ezrin (68). Colocalization of NCX1 with mAKAP and PKA-RI-NCX1 has been identified in the sarcolemma and in Z-line/T-tubules by us and others (48,49,67). The mAKAP has been localized in the sarcoplasmic reticulum, in the perinuclear region, and in Z-line/T-tubular regions in cells (37,47,69).…”
Section: Regulators and Ncx1mentioning
confidence: 84%
“…Normal function of the Na/Ca exchanger requires proper biophysical properties and precise localization at excitable cardiac membranes including the sarcolemma and cardiomyocyte transverse-tubule surfaces (5)(6)(7)(8)(9). Whereas the biophysical features of the cardiac Na/Ca exchanger are widely studied and well defined (10 -13), the molecular mechanisms required for the targeting and retention of the Na/Ca exchanger at specialized membrane domains in cardiomyocytes are unknown.…”
mentioning
confidence: 99%
“…Using these incompletely fractionated cardiac membranes and radiolabeled DHPs, cardiac DHP receptors were suggested to be localized at surface sarcolemma and T-tubules [ 11,141. The cardiac Na+/Ca'+ exchanger, on the other hand, has recently been immnohistochemically localized to surface sarcolemma as well as T-tubules in guinea pig and rat heart [15,16].…”
Section: Y Iwata Et Al I Febs Letters 355 (1994) 65-68mentioning
confidence: 99%